Research progress of protein haze in white wines - Zhaolong Liu; Le Xu; Jun Wang; Changqing Duan; Yanfeng Sun; Qingsen Kong; Fei He (Food Science and Human Wellness)
Protein haze was one of the main causes of the instability of white wines. Proteins that caused haze or precipitation in white wines mainly came from grape fruits, and their compositions and contents were affected by many factors such as fruit diseases, harvesting methods and water stress. Unstable wine proteins were usually pathogenesis-related (PR) proteins of grapes, mainly chitinases and thaumatin-like proteins (TLPs), which had lower isoelectric point (pI) and smaller molecular weight, and were highly resistant to the low pH values of wines and the protease hydrolysis during fermentation. At present, the technology of protein stabilization and clarification in white wines mainly included bentonite fining, heat treatment, enzymatic hydrolysis, polysaccharide treatment and ultrafiltration methods. Among them, the most commonly used method was bentonite treatment. In this paper, the research progresses of the origin, mechanism and influencing factors of the unstable proteins in white wines were summarized, and the applications, advantages and disadvantages of various clarification techniques were also concluded, in order to provide some support for the theoretical and technological research of the protein stability in white wines in the future.